Self-healing concrete as a prospective construction material: a review - Amran, Mugahed; Onaizi, Ali M.; Fediuk, Roman; Vatin, Nikolai Ivanovicn; Muhammad Rashid, Raizal Saifulnaz; Abdelgader, Hakim; Ozbakkaloglu, Togay (MDPI, 2022)
Concrete is a material that is widely used in the construction market due to its availability and cost, although it is prone to fracture formation. Therefore, there has been a surge in interest in self-healing materials, particularly self-healing capabilities in green and sustainable concrete materials, with a focus on different techniques offered by dozens of researchers worldwide in the last two decades. However, it is difficult to choose the most effective approach because each research institute employs its own test techniques to assess healing efficiency. Self-healing concrete (SHC) has the capacity to heal and lowers the requirement to locate and repair internal damage (e.g., cracks) without the need for external intervention. This limits reinforcement corrosion and concrete deterioration, as well as lowering costs and increasing durability. Given the merits of SHCs, this article presents a thorough review on the subject, considering the strategies, influential factors, mechanisms, and efficiency of self-healing. This literature review also provides critical synopses on the properties, performance, and evaluation of the self-healing efficiency of SHC composites. In addition, we review trends of development in research toward a broad understanding of the potential application of SHC as a superior concrete candidate and a turning point for developing sustainable and durable concrete composites for modern construction today. Further, it can be imagined that SHC will enable builders to construct buildings without fear of damage or extensive maintenance. Based on this comprehensive review, it is evident that SHC is a truly interdisciplinary hotspot research topic integrating chemistry, microbiology, civil engineering, material science, etc. Furthermore, limitations and future prospects of SHC, as well as the hotspot research topics for future investigations, are also successfully highlighted.